Comparative complete scheme and booster effectiveness of COVID‐19 vaccines in preventing SARS‐CoV‐2 infections with SARS‐CoV‐2 Omicron (BA.1) and Delta (B.1.617.2) variants: A case–case study based on electronic health records - Kislaya, Irina (2023)
Background: Information on vaccine effectiveness in a context of novel variants of concern (VOC) emergence is of key importance to inform public health policies. This study aimed to estimate a measure of comparative vaccine effectiveness between Omicron (BA.1) and Delta (B.1.617.2 and sub-lineages) VOC according to vaccination exposure (primary or booster). Methods: We developed a case–case study using data on RT-PCR SARS-CoV2-positive cases notified in Portugal during Weeks 49–51, 2021. To obtain measure of comparative vaccine effectiveness, we compared the odds of vaccination in Omicron cases versus Delta using logistic regression adjusted for age group, sex, region, week of diagnosis, and laboratory of origin. Results: Higher odds of vaccination were observed in cases infected by Omicron VOC compared with Delta VOC cases for both complete primary vaccination (odds ratio [OR] = 2.1; 95% confidence interval [CI]: 1.8 to 2.4) and booster dose (OR = 5.2; 95% CI: 3.1 to 8.8), equivalent to reduction of vaccine effectiveness from 44.7% and 92.8%, observed against infection with Delta, to 6.0% (95% CI: 29.2% to 12.7%) and 62.7% (95% CI: 35.7% to 77.9%), observed against infection with Omicron, for complete primary vaccination and booster dose, respectively. Conclusion: Consistent reduction in vaccine-induced protection against infection with Omicron was observed. Complete primary vaccination may not be protective against SARS-CoV-2 infection in regions where Omicron variant is dominant.